Novel meta-heuristic bald eagle search algorithm for single objective unconstraint functions in global optimization problem - Ibrahim, Hassan Abdul Sattar (Tanjong Malim, 2024)
Novel meta-heuristic bald eagle search algorithm for single objective unconstraint functions in global optimization problem by Ibrahim, Hassan Abdul Sattar